2022
DOI: 10.3389/fonc.2022.846840
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Energy CT Radiomics of the Regional Largest Short-Axis Lymph Node Can Improve the Prediction of Lymph Node Metastasis in Patients With Rectal Cancer

Abstract: ObjectiveTo explore the value of dual-energy computed tomography (DECT) radiomics of the regional largest short-axis lymph nodes for evaluating lymph node metastasis in patients with rectal cancer.Materials and MethodsOne hundred forty-one patients with rectal cancer (58 in LNM+ group, 83 in LNM- group) who underwent preoperative total abdominal DECT were divided into a training group and testing group (7:3 ratio). After post-processing DECT venous phase images, 120kVp-like images and iodine (water) images wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…( 71 ) also conducted a related study and showed that AI performed far better than experienced gastrointestinal pathologists. In addition, CT- or MRI-based imaging histology has many applications, including assessing pathological responses after radiotherapy or chemotherapy ( 72 ) and predicting colon cancer infiltration and metastasis ( 73 , 74 ). The duration of keyword bursts was long before 2016 and became shorter after 2016 ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…( 71 ) also conducted a related study and showed that AI performed far better than experienced gastrointestinal pathologists. In addition, CT- or MRI-based imaging histology has many applications, including assessing pathological responses after radiotherapy or chemotherapy ( 72 ) and predicting colon cancer infiltration and metastasis ( 73 , 74 ). The duration of keyword bursts was long before 2016 and became shorter after 2016 ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, radiomics parameters provide more quantitative information than traditional parameters used by radiologists. In 2022, Wang et al [53] explored the relationship between DECT radiomics features of regional largest short-axis LNs and metastasis in patients with rectal cancer. After post-processing the venous phase images from DECT, 120 kVp-like images and iodine images were obtained, from which a substantial set of 833 features were extracted.…”
Section: Radiomics and Artificial Intelligence In Dectmentioning
confidence: 99%
“…Radiomics is an ever-advancing field and its use has been applied clinically to other novel imaging techniques including dual energy CT, diffusion- weighted imaging (DWI), intravoxel incoherent motion DWI (IVIM-DWI), functional MRI, BOLD MRI and perfusion studies. 163–169 It is inevitable that future directions will see increasing application of radiomics to such novel imaging techniques for the purposes of advancing diagnostic and prognostication in oncology and guiding optimal immunotherapy treatments. In-depth characterisation of the whole TME by imaging can be achieved unlike biopsies which can only sample a small fraction of the heterogeneous TME.…”
Section: Radiomicsmentioning
confidence: 99%